On the representation of a number as a sum of the k-th powers in an arithmetic progression - Prosyanyuk, N.S. (Algebra and Discrete Mathematics, 2003)
In this paper we obtain the asymptotic formula for a natural n ≤ x which representate as a sum of two non-negative k-th powers in an arithmetic progression.